Auto Intensity Control of Street Lights cum shading during rain Using Arduino - Ghosh, Sounik; Bhunia, Siddhartha Sankar; Samanta, Annesa (International Journal of Computer Sciences and Engineering, 2025)
A vast quantity of electrical power of various countries is consumed in lighting the streets. For a specific period of time, the vehicles passes with low rate and some parts of the streets are not occupied by vehicles, in that time there is wastage. The main aim of this paper is to develop an automatic system by which energy will be conserved as well as public shelter will be given, and doing so, few more homes will be lightened and we will be able to give shelter to everyone in road during sudden rainfall. The proposed work is accomplished by using Arduino UNO microcontroller and sensors to control the wastage of electricity and the shading during rain. Meanwhile, a counter is set to count the rain drops. This proposed work will be useful for reducing the wastage of unused electricity and public shelter in sudden situation.